PEMBERDAYAAN KELOMPOK TANI HUTAN GREEN LAWU DI DESA BERJO KECAMATAN NGARGOYOSO KARANGANYAR - Restik Bunga Widarizki; Yosafat Hermawan Trinugraha (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
Community empowerment is an important effort to improve the capacity, independence, and welfare of communities, especially those living around forest areas. This study aims to analyze the role of stakeholders in empowering the Green Lawu Forest Farmer Group (KTH Green Lawu) in Berjo Village, Ngargoyoso District, Karanganyar Regency, and to identify the impacts and challenges faced by the group in the empowerment process. This study employed a qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation. The informants consisted of administrators and members of KTH Green Lawu, Berjo Village Government, managers of Tahura KGPAA Mangkunagoro I, forestry extension officers, and Pertamina as a supporting stakeholder through its Corporate Social Responsibility (CSR) program. Data were analyzed using the interactive model of Miles and Huberman through data reduction, data display, and conclusion drawing. The results show that stakeholders play an important role in the empowerment process through facilitative, educational, technical, and representative functions. These roles were manifested through the provision of facilities, mentoring, training, opening access to networks, and support for productive business development. The empowerment process has had positive impacts on improving members’ capacity, creating economic opportunities, strengthening group institutions, and increasing community awareness of environmental conservation. However, the group still faces several challenges, including limited human resources, uneven member participation, limited business capital, and dependence on external stakeholders. Therefore, the empowerment of KTH Green Lawu has progressed fairly well, but it is still at the capacity-building stage and has not fully achieved group independence.